(untitled) (CIPEEX, 2022)
THE COVID-19 PANDEMIC RESULTED IN ADOPTION OF SOCIAL ISOLATION IN ORDER TO CONTAIN THE ACCELERATED TRANSMISSION OF THE SARS-COV-2 VIRUS, CONSEQUENTLY, THOUSANDS OF CHILDREN HAD THEIR DAILY ACTIVITIES CEASED AND SUMMARIZED TO THE HOME AND FAMILY NUCLEUS. THEREFORE, THE PRESENT ANALYSIS IS AN INTEGRATIVE LITERATURE REVIEW THAT AIMS TO DESCRIBE THE EFFECT OF SOCIAL ISOLATION ON CHILD DEVELOPMENT IN THE COVID-19 CONTEXT. TWENTY ARTICLES FROM PUBMED, GOOGLE SCHOLAR, SCIELO AND LILACS DATABASES WERE USED, APPLYING THE DESCRIPTORS €ŒDESENVOLVIMENTO INFANTIL€, €ŒEDUCAO INFANTIL€, €ŒISOLAMENTO SOCIAL€, €ŒPANDEMIA€. ABOUT THE ANALYSES ON VIRTUAL EDUCATION, INTERMEDIATE RESULTS WERE OBTAINED IN RELATION TO LEARNING AND AVAILABILITY OF DEVICES, IMPLYING DIVERGENCES BETWEEN SOCIAL CLASSES, GENDERS AND ETHNICITY. STILL SOCIAL AND EMOTIONAL DEVELOPMENT, PRESENTED NEGATIVE RESULTS INDICATING POSTTRAUMATIC DISORDER, NUTRITIONAL DEFICIT AND VULNERABILITY SITUATION. GIVEN THE ABOVE, THE PRESENT STUDY IDENTIFIED SUPERIORITY OF CHILD PHYSICAL HEALTH NEEDS IN RELATION TO EDUCATIONAL AND EMOTIONAL NEEDS, STILL UNKNOWN AT THAT TIME.